If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=3(7x+7)+3(5-3x)
We move all terms to the left:
12-(3(7x+7)+3(5-3x))=0
We add all the numbers together, and all the variables
-(3(7x+7)+3(-3x+5))+12=0
We calculate terms in parentheses: -(3(7x+7)+3(-3x+5)), so:We get rid of parentheses
3(7x+7)+3(-3x+5)
We multiply parentheses
21x-9x+21+15
We add all the numbers together, and all the variables
12x+36
Back to the equation:
-(12x+36)
-12x-36+12=0
We add all the numbers together, and all the variables
-12x-24=0
We move all terms containing x to the left, all other terms to the right
-12x=24
x=24/-12
x=-2
| 1.90x+6=2.50x+2 | | -4x-9=-16 | | 10+8=6n | | -4x-9=-11 | | (x+7)^3=4096 | | 8a+3a-6a=-17+27 | | 5t^2+15t-50=0 | | 28=16+6q | | 6b-12=4b+16 | | 3f+5=323f | | 4x+2-7=x+7 | | 36+-2z=-28 | | 7b+23=58 | | 18-3y=11+y | | 1+4x-6x=1-8x | | 9+8a=-3 | | 2/3(3x+)=14 | | 4(1-x)=-5x-2 | | 0.5x^2-0.5x-0.025=0 | | 20y-18=5(3y+4)+2 | | 6+3(2x-7)=3x-9 | | 46=x-20 | | 2(x-1)=6x+10 | | 4-(2x+4)=12 | | 2(g+18)=62 | | 16-2x=31+3 | | 3(1q+4)+4q+1=0 | | 10n/3-2n=-2/5 | | -13-7x=8-4x | | 2x-10+x+30+x=180 | | 4(1-6)=-5x-2 | | 3x+78=82 |